(untitled) (Mustansiria Dental Journal, 2018)
The denture retention and stability are dependent on saliva flow rate and quality, patients with dry mouth may have problems with the stability or comfort of maxillary complete dentures. Dry mouth is a common feature in the elderly, but is not clear what proportion of incidences is related to functional disturbances and whether age persue and Gender play a role. The aim of this study is to determine the effect of age on unstimulated (Resting) whole and stimulated saliva flow rates. It was determined in 100 unmedicated, healthy individuals wearing complete dentures. The subjects were divided into two age groups: group A(< 70 years), group B(> 70 years). A significant decrease in the secretion rates of unstimulated whole saliva in relation to age was observed in the study population (p< 0.001). Females had significantly lower mean flow rates than males for unstimulated (resting) whole saliva.